2021
DOI: 10.1111/mec.15990
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the predictive role of temperature in the gut microbiota of the sea urchin Echinometra sp. EZ across spatial and temporal gradients

Abstract: The microbiome is important in shaping organismal biology in a wide range of eukaryotic species and has been shown to play critical roles in host physiological functions and susceptibility to disease (Bayer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Although these results contrast with previous experimental studies on adult urchins (spines, gut) showing that the urchin microbial community is stable under exposure to OW/OA (Brothers et al, 2018; Webster et al, 2016), the discrepancy in microbial responses may be explained by the different tissue types as well as the extended exposure periods investigated within this study. Indeed, Ketchum et al (2021) recently confirmed that temperature‐driven microbial shifts occur in the gut of the urchin Echinometra sp. EZ in natural conditions, suggesting that temperature can be a predictor of community variation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although these results contrast with previous experimental studies on adult urchins (spines, gut) showing that the urchin microbial community is stable under exposure to OW/OA (Brothers et al, 2018; Webster et al, 2016), the discrepancy in microbial responses may be explained by the different tissue types as well as the extended exposure periods investigated within this study. Indeed, Ketchum et al (2021) recently confirmed that temperature‐driven microbial shifts occur in the gut of the urchin Echinometra sp. EZ in natural conditions, suggesting that temperature can be a predictor of community variation.…”
Section: Discussionmentioning
confidence: 96%
“…Sea urchins are an emerging model for investigating animal–microbe symbiosis (Carrier et al, 2021), showing a re‐shaping of the bacterial communities during major developmental transitions, from pelagic larvae to benthic juveniles and adults, with microbes inferred to contribute to larval immunity and nutrition in some species (Carrier et al, 2021; Carrier & Reitzel, 2019, 2020; Schuh et al, 2020). Urchins are susceptible to changing climate, in particular, during larval life stages (Byrne & Przeslawski, 2013), though little is known about the effects of OW and OA on microbial dynamics in adult urchins and early developmental stages (Brothers et al, 2018; Carrier & Reitzel, 2020; Ketchum et al, 2021; Webster et al, 2016). Along with an important role in reef resilience through its grazing activity, Echinometra sp.…”
Section: Introductionmentioning
confidence: 99%
“…Microbiome assembly depends on the host's evolutionary history and the environment [38][39][40][41]. One of these two factors is often more influential [39,40], but which host gene(s) or environmental parameter(s) influences these interactions often remains elusive (but see [42,43]). Furthermore, recent efforts have increased the availability of hologenomes to enable the underlying genetic factors of these evolutionarily ancient partnerships to be determined [41,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results reported in the sea urchin ( Echinometra sp. EZ ) with gut microbiota varying across thermally variable habitats and displaying temporal shifts correlated with temperature ( Ketchum et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%